1999
DOI: 10.1007/s002109900101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mechanisms involved in the acute airway toxicity induced by parathion

Abstract: Organophosphates are still widely used worldwide and cause thousands of intoxications every year. In this work we investigated the mechanisms of parathion (Pth) airway toxicity, using biochemical and functional approaches. A plethysmographic technique for unrestrained guinea pigs was used to analyze Pth-induced modifications of airway mechanics and responsiveness to acetylcholine (ACh: 0.1-3.2 mg/ml, 2-min inhalation each dose). The isolated perfused rabbit lung preparation was used to study the acute effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 32 publications
4
32
0
2
Order By: Relevance
“…Recent animal studies have demonstrated that organophosphates induce airway hyperreactivity, potentially at doses below those causing acetylcholinesterase inhibition (6,7,21). Pesticides may also modulate inflammatory responses to other farm exposures, such as endotoxin and allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal studies have demonstrated that organophosphates induce airway hyperreactivity, potentially at doses below those causing acetylcholinesterase inhibition (6,7,21). Pesticides may also modulate inflammatory responses to other farm exposures, such as endotoxin and allergens.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study using an in vivo model of organophosphate poisoning, we (35) found that guinea pigs with an ongoing parathion-induced bronchoobstruction responded to salbutamol administration with a transient bronchodilation, which was followed by a returning of the bronchoobstruction. Those results allowed us to speculate that salbutamol triggered some obstructive mechanism that rapidly counteracted its relaxing action.…”
mentioning
confidence: 82%
“…Mechanical ventilation supplies a constant V I so a reduction in this ratio is a result of decreased V E possibly due to severe loss of pulmonary compliance or outright obstruction of the lower airways resulting in a rupture of the tracheal seal, thereby causing a reduction in expired volume compared to inspired volume. Future studies using this animal model could benefit from measurement of airway pressure, which we would expect to increase due to pulmonary toxicity of OP [10,18].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Acute effects of poisoning include central apnea [1][2][3][4], seizures [5,6], bronchorrhea, bronchoconstriction, muscle weakness, myosis, urination, and salivation [7][8][9][10]. The morbidity and mortality from acute OP poisoning is attributed to respiratory failure [11] but the relative contributions of the central and peripheral effects in producing collapse of the respiratory system [12] is unclear.…”
Section: Introductionmentioning
confidence: 99%